Aluminium nanoparticle-based ultra-wideband high-performance polarizer - Md. Shariful Islam; Ahmed Zubair (Heliyon)
The polarizer-based device industry is expanding quickly, requiring high-quality research on nanoscale wideband polarizers. Here, we investigated the possibility of utilizing Al dimer nanostructures on broad-band polarizers. Metals are always considered promising candidates for reflection-based polarizer development because of their high extinction ratio. This study proposes a novel nanoparticle polarizer comprised of semi-immersed Al nano-dimers with a 200 nm radius on a CaF2 substrate. Our proposed nano-dimer-based design demonstrated impressive polarization anisotropy in the near-infrared (NIR) and THz ranges than conventional wire-grid-based ones. This study includes calculating performance parameters for the extraction of the proposed polarizer, including insertion loss, extinction ratio (ER), Mueller matrix values, and polarization ellipse diagram. The finite-difference time-domain (FDTD) simulation-based results suggested obtaining more than 55 dB extinction ratio for the 0.2 to 9 THz range. In the THz region, simulation results suggest impressively better performance than conventional wire-grid polarizers. In THz frequency range, our proposed polarizer demonstrated its extinction ratio of up to 60 dB. The average extinction ratio and insertion loss over the 1–1665 μm wavelength were 29.01 dB and ∼1 dB, respectively. The idea of Al dimer and the insight gained from the results extracted from the rigorous simulation report suggested a great opportunity for developing micro-scale metallic wideband polarizers.